2019
DOI: 10.3390/molecules24061054
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside L Inhibits Proliferation of Liver and Esophageal Cancer Cells by Inducing Senescence

Abstract: Senescence is an irreversible state of cell cycle arrest that can be triggered by multiple stimuli, such as oxygen reactive species and DNA damage. Growing evidence has proven that senescence is a tumor-suppressive approach in cancer treatment. Therefore, developing novel agents that modulate senescence may be an alternative strategy against cancer. In our study, we investigated the inhibitory effect of gypenoside L (Gyp-L), a saponin isolated from Gynostemma pentaphyllum, on cancer cell growth. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…However, gypenoside L could render cancer cells more sensitive to chemotherapy such as cisplatin by impairing the protective autophagy. Based on this, gypenoside L could be explored as a promising agent for solving the problem of resistance [ 16 ].…”
Section: Pharmacological Properties Of Gpmentioning
confidence: 99%
“…However, gypenoside L could render cancer cells more sensitive to chemotherapy such as cisplatin by impairing the protective autophagy. Based on this, gypenoside L could be explored as a promising agent for solving the problem of resistance [ 16 ].…”
Section: Pharmacological Properties Of Gpmentioning
confidence: 99%
“…ZEHUA WANG 1,2* , JIANWEN GAO 3-5* , HAIOU LIU 1,2 , YUKO OHNO 3 and cONGJIAN XU 1,2,6 1 Obstetrics and Gynecology Hospital of Fudan University; 2 Shanghai Key Laboratory of Female Reproductive Endocrine Related diseases, Shanghai 200011, P.R. china; 3 department of Mathematical Health Science, Graduate School of Medicine, Osaka University, Suita, Osaka 565-0871, Japan; 4 School of Medical Engineering, Ma'anshan University, Ma'anshan, Anhui 243100; 5 Major of Biotechnological Pharmaceutics, Shanghai Pharmaceutical School, Shanghai 200135; 6 department of Obstetrics and Gynecology of Shanghai Medical School, Fudan University, Shanghai 200032, P.R. china Cellular morphological changes.…”
Section: Targeting Senescent Cells and Tumor Therapy (Review)mentioning
confidence: 99%
“…Cell senescence plays important roles in non-disease-related physiological processes, including embryo development, wound healing, tissue repair and aging ( 1 ). A large number of previously published studies have demonstrated that cell senescence plays an important role in the inhibition of potential cancer cell proliferation pathways ( 2 - 4 ). However, as the detailed scientific knowledge in this field continues to expand, it has been demonstrated that senescent cells also secrete a variety of cytokines, chemokines, matrix-remodeling proteases and growth factors to form the senescence-associated secretory phenotype (SASP), which is a 'double-edged sword' in that it may either inhibit or promote tumor formation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are important resources for anticancer drugs ( 11 , 12 ), such as gypenoside L and matrine. Studies have demonstrated that gypenoside L inhibited the proliferation of esophageal cancer cells and enhanced the sensitivity of them to chemotherapy ( 13 ), and matrine increased the inhibition rate of cell proliferation by inducing cell autophagy ( 14 ). Therefore, there is an urgent requirement to develop natural medicine with high efficiency and minimal side effects to improve the treatment of esophageal cancer and improve population health.…”
Section: Introductionmentioning
confidence: 99%